2019
DOI: 10.1080/02713683.2019.1645184
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 is a Modifier of Oxygen-Induced Retinopathy Severity

Abstract: Purpose/Aim: Abnormal activation of signaling pathways related to angiogenesis, inflammation, and oxidative stress has been implicated in the pathophysiology of retinopathy of prematurity (ROP), a leading cause of blindness in pre-term infants. Therapies for ROP include laser and antivascular endothelial growth factor agents. However, these therapies have side effects, and even with adequate treatment, visual acuity can be impaired. Novel therapeutic options are needed. Stanniocalcin-1 (STC-1) is neuroprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition to calcium metabolism, STC-1 has been shown to be cytoprotective by regulating oxidative stress [38][39][40][41][42][43] and inflammation, [43][44][45][46] and be neuroprotective for cerebral neurons, retinal photoreceptors, and retinal ganglion cells [47][48][49][50]. More recently, we demonstrated that STC-1 also has a role in development of the oxygen induced retinopathy stress response [51]. Though recent work has shown that megalin can act as a shuttle protein to transport STC-1 to the mitochondria, a potential cellular receptor has…”
Section: Plos Onementioning
confidence: 81%
“…In addition to calcium metabolism, STC-1 has been shown to be cytoprotective by regulating oxidative stress [38][39][40][41][42][43] and inflammation, [43][44][45][46] and be neuroprotective for cerebral neurons, retinal photoreceptors, and retinal ganglion cells [47][48][49][50]. More recently, we demonstrated that STC-1 also has a role in development of the oxygen induced retinopathy stress response [51]. Though recent work has shown that megalin can act as a shuttle protein to transport STC-1 to the mitochondria, a potential cellular receptor has…”
Section: Plos Onementioning
confidence: 81%
“…Another molecule that seems to have a defensive effect against oxidative stress is stanniocalcin-1 (STC-1), which is a neuroprotective protein with anti-inflammatory and antioxidative stress properties [56]. STC-1 plays a role in the OIR stress response and development of pathologic vascular features in rodent OIR models by regulating VEGF levels [56]. STC-1 is a multifunctional protein that is upregulated by cellular stresses [57][58][59][60].…”
Section: Stanniocalcin-1mentioning
confidence: 99%
“…The present data suggest STC-1 modulates OIR severity, in part, due to its effect on VEGF production. The reduction of avascular and neovascular retinas in the presence of STC-1 might be associated with neuroprotective and anti-VEGF effects [56,[63][64][65].…”
Section: Stanniocalcin-1mentioning
confidence: 99%
“…Moreover, the counteracting effects of STC1 on LPS-induced lung injury [ 15 ] or ischemic cardiac injury in mice [ 16 ], via inhibition of inflammatory cascades or suppression on monocytes/macrophages recruitment were revealed respectively. The anti-inflammatory effects of STC1 on other models, like osteoarthritis [ 17 ], and retinopathy [ 18 ] were reported.…”
Section: Introductionmentioning
confidence: 99%